Sistem Kandang Ayam Petelur Otomatis Dengan Memanfaatkan Open-Source Hardware - Krsna Elian Panji Restu; Made Liandana; I Komang Agus Ady Aryanto; Bagus Made Sabda Nirmala (Universitas Katolik Musi Charitas, 2022)
In general, laying hen farms still provide feed using a conventional system by sprinkling the feed in the feeding area along the cage and moving from one cage to another. Laying hens' manure that is still cleaned by dredging the manure is then collected in sacks or by spraying water, as well as collecting eggs manually by picking up eggs along the length of the cage. This activity is still not effective in maintaining and maintaining the cage because it still requires a lot of work. Therefore we need a facility for laying hens that can work automatically. This automatic laying hen cage can help laying hen breeders in providing feed, cleaning manure, collecting chicken eggs automatically and calculating egg yields easily and can monitor the temperature and humidity of the layer hen coops in real time. This system uses modules and sensors that are linked and connected to a microcontroller which can be monitored by the user through the Blynk application on the user's smartphone. The system is built using existing components in the form of sensor modules that are easy to get on the market at an affordable price, namely the use of Arduino Atmega2560 as a microcontroller, LCD to display the results of data obtained in the cage, Relays for motorbike manure switches and egg collection , the motor driver Ln298 as a motor control regulator, Esp8288 for wifi networks, DHT22 for temperature and humidity measurements in the enclosure, and RTC DS3231 for digital timing in the enclosure. These tools are built not too complex so that breeders or users can easily use and carry out maintenance if one of the components of the tool is damaged so that it is easy to replace.